Improving Civic Literacy on Population and Government in Elementary Schools: A Quasi-Experimental Study Based on Contextual Learning - Kdianti, Gita; Nadhifah, Dinah; Zaid, Muhammad Idris Maas (Yayasan Zia Salsabila, 2023)
The low level of civic literacy among elementary school students, particularly in understanding Indonesia's population and governmental system, poses a critical challenge in basic education. This study aims to evaluate the effectiveness of contextual learning strategies in improving students’ civic literacy. Employing a quasi-experimental approach with qualitative descriptive methods, the study was conducted at an elementary school in Kendari City. Data were collected through observations, interviews, and student learning documentation. The findings demonstrate that contextual learning significantly enhances students’ understanding of governmental structures, citizen roles, and population issues by engaging them in relevant and participatory learning experiences. The study’s outcomes highlight improvements in students' critical awareness, multimodal communication, and active classroom involvement. These findings underscore the importance of contextualized, student-centered civic education that is grounded in local experiences. The study contributes to the development of participatory pedagogy and advocates for inclusive civic education models within Indonesia’s primary education system.